PROSPEK PENGEMBANGAN PROGRAM KEMITRAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI BENIH BUNCIS PADAPROGAM KEMITRAAN (CONTRACTFARMING)PT. BENIH CITRA ASIA - Joni Murti Mulyo Aji; Yuli Hariyati; Imaniar Agustina (Agriekonomika, 2012)
ABSTRACTBeans (Phaseolusvulgaris .L.)have been known as an important vegetable for a long time. Although the use ofgreen beans as daily consumptiontendsto decline, the demandas rawmaterial in agribusinessindustryandotherstendsto increase. This situation open the opportunity for PT. Benih CitraAsia (BCA),a horticulture breeding company, to collaborate with farmers producingseeds including green beans seedthrough contract farming arrangement. This research aims to identify opportunities andbenefits of involving in a contractfarming arrangement for farmers, factorsaffecting income,income’s value and farm management cost efficiency. This research was conducted in Wuluhan Sub District, Jember Regency. The data was analyzedby using SWOTanalysis, the multiplier linear regression model, income analysis andR/Cratio. Resultsshowed that: (1) contract-farming arrangement located in SWOT whitearea(ideal). It also indicated that there was strongopportunityandbenefit for both parties involved. (2) Seed cost (X2), fertilizer costs(X3), labor costs(X5) andtotalproduction(X6) were found as factors influencing farmers’ income with significant level of 95%. (3) The average income per hectare of beans farming in Wuluhan Sub District Jember Regency was Rp.5.248.213,10. (4) R/C ratio of this farm management was more than one (1,43),it indicated that the using of cost in green beans farm management was efficient. Keywords: contractfarming, incomefactors, cost efficiency, income.